Bendix: intuitive helix geometry analysis and abstraction. - Dahl, A; Chavent, M; Sansom, MS (2012)
UNLABELLED: The flexibility of α-helices is important for membrane protein function and calls for better visualization and analysis. Software is presented that quantifies and projects the helix axis evolution over time, with the choice of uniform or analytic heatmap graphics according to the local geometry. Bendix supports static, molecular dynamics, atomistic and coarse-grained input. AVAILABILITY AND IMPLEMENTATION: Bendix source code and documentation, including installation instructions, are freely available at http://sbcb.bioch.ox.ac.uk/Bendix. Bendix is written in Tcl as an extension to VMD and is supported by all major operating systems.